The Effect of Regional Taxes, Regional Levies, Local Original Revenues on District and City Regional Expenditures in East Kalimantan Province in 2017-2021 - Dinar Ambarita; Astri Elvani; Ibrohim Ibrohim (Pelopor Publikasi Akademika, 2023)
This study aims to determine the influence of Regional Taxes, Regional Levies, and Regional Own Revenue on Regional Expenditure in the Regency or City of the Province of East Kalimantan in 2017-2021. The population in this study were districts or cities in the province of East Kalimantan, which has 7 regencies and 3 cities with 5 years of observation. As for those who meet the criteria in this study as many as 8 districts or cities. The method used in collecting data in this study used purposive sampling. The results of the study show that the t test and f test have their respective effects on variables, where the influence of regional taxes, regional levies, and regional original income significantly affects regional spending.